Magyar diákok hollandiai tanulmányai a kora újkorban - Bozzay, Réka (Gerundium, 2017)
The Study of Hungarian Students at Dutch Universities in the Early Modern Age. The aim of this paper is to give an insight into the study of Hungarian sholars at Dutch universities in the Early Modern Age. The method based primarily on numerical data concerning the number of students at a university in different periods divided by majors; previous educational background, SES status and occupation. The analysis also concerns the financial support of universities, provinces and cities students received at that time.